2021
DOI: 10.3390/polym14010057
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Morphology in the Nanoscale of NH4CN Polymers Synthesized by Microwave Radiation: A Comparative Study

Abstract: A systematic study is presented to explore the NH4CN polymerization induced by microwave (MW) radiation, keeping in mind the recent growing interest in these polymers in material science. Thus, a first approach through two series, varying the reaction times and the temperatures between 130 and 205 °C, was conducted. As a relevant outcome, using particular reaction conditions, polymer conversions similar to those obtained by means of conventional thermal methods were achieved, with the advantage of a very signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…In any case, comparatively, for all the time ranges studied here, the MWR leads to lower yields for insoluble NH 4 CN polymers at any temperature than CTH, except for the two unexpected points indicated at 67 min. This general result is in agreement with the data previously reported, which indicated that an increase in the temperature leads to lower conversion values [ 35 , 36 ] and that the MWR improves the oxidation and hydrolysis processes of cyanide and the intermediate products during the polymerization reactions, decreasing the overall yield for the insoluble macromolecular fractions [ 30 , 37 ]. Therefore, an important effect of the MWR is to reduce the hydrothermal production of insoluble cyanide polymers.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…In any case, comparatively, for all the time ranges studied here, the MWR leads to lower yields for insoluble NH 4 CN polymers at any temperature than CTH, except for the two unexpected points indicated at 67 min. This general result is in agreement with the data previously reported, which indicated that an increase in the temperature leads to lower conversion values [ 35 , 36 ] and that the MWR improves the oxidation and hydrolysis processes of cyanide and the intermediate products during the polymerization reactions, decreasing the overall yield for the insoluble macromolecular fractions [ 30 , 37 ]. Therefore, an important effect of the MWR is to reduce the hydrothermal production of insoluble cyanide polymers.…”
Section: Resultssupporting
confidence: 93%
“…Cyanide polymerization assisted by MWR is described using three different temperatures, 170, 190 and 205 °C. These temperatures were chosen on the basis of a previous report about microwave-driven cyanide polymerization [ 37 ]. In addition, syntheses at 80 °C using CTH have been considered representative control experiments to determine the effect of the MWR.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations